High level xylitol production by Pichia fermentans using non-detoxified xylose-rich sugarcane bagasse and olive pits hydrolysates. (December 2021) - Narisetty, Vivek; Castro, Eulogio; Durgapal, Sumit; Coulon, Frederic; Jacob, Samuel; Kumar, Dinesh; Kumar Awasthi, Mukesh; Kishore Pant, Kamal; Parameswaran, Binod; Kumar, Vinod
Graphical abstract: Highlights: Xylitol production from non-detoxified agro-industrial residues using P. fermentans . Optimum glucose to xylose ratio and feed composition improved Xylitol accumulation. Xylitol titer of 86.6 g/L with yield of 0.75 g/g was achieved from SCB hydrolysate. OP hydrolysate resulted in xylitol titers of 71.9 g/L with a yield of 0.74 g/g. Abstract: Hemicellulosic sugars, the overlooked fraction of lignocellulosic residues can serve as potential and cost-effective raw material that can be exploited for xylitol production. Xylitol is a top platform chemical with applications in food and pharmaceutical industries. Sugarcane bagasse (SCB) and olive pits (OP) are the major waste streams from sugar and olive oil industries, respectively. The current study evaluated the potential of Pichia fermentans for manufacturing of xylitol from SCB and OP hydrolysates through co-fermentation strategy. The highest xylitol accumulation was noticed with a glucose and xylose ratio of 1:10 followed by feeding with xylose alone. The fed-batch cultivation using pure xylose, SCB, and OP hydrolysates, resulted in xylitol accumulation of 102.5, 86.6 and 71.9 g/L with conversion yield of 0.78, 0.75 and 0.74 g/g, respectively. The non-pathogenic behaviour and ability to accumulate high xylitol levels from agro-industrial residues demonstrates the potential of P. fermentans as microbial cell factory.